4(2+2r)-2(-r+1)=6r+-2r

Simple and best practice solution for 4(2+2r)-2(-r+1)=6r+-2r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2+2r)-2(-r+1)=6r+-2r equation:


Simplifying
4(2 + 2r) + -2(-1r + 1) = 6r + -2r
(2 * 4 + 2r * 4) + -2(-1r + 1) = 6r + -2r
(8 + 8r) + -2(-1r + 1) = 6r + -2r

Reorder the terms:
8 + 8r + -2(1 + -1r) = 6r + -2r
8 + 8r + (1 * -2 + -1r * -2) = 6r + -2r
8 + 8r + (-2 + 2r) = 6r + -2r

Reorder the terms:
8 + -2 + 8r + 2r = 6r + -2r

Combine like terms: 8 + -2 = 6
6 + 8r + 2r = 6r + -2r

Combine like terms: 8r + 2r = 10r
6 + 10r = 6r + -2r

Combine like terms: 6r + -2r = 4r
6 + 10r = 4r

Solving
6 + 10r = 4r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-4r' to each side of the equation.
6 + 10r + -4r = 4r + -4r

Combine like terms: 10r + -4r = 6r
6 + 6r = 4r + -4r

Combine like terms: 4r + -4r = 0
6 + 6r = 0

Add '-6' to each side of the equation.
6 + -6 + 6r = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 6r = 0 + -6
6r = 0 + -6

Combine like terms: 0 + -6 = -6
6r = -6

Divide each side by '6'.
r = -1

Simplifying
r = -1

See similar equations:

| M-8=3m+2 | | 21=6(5r-2) | | 3x+3-9=3+7-4 | | 2x+3(x-8)=9-5x | | 8x-25=6x-5 | | 100/15 | | -7x+23=-21-31x | | 36k^3=35 | | 2x+2+6x+1=5x-21 | | -0.7x+2.3=-2.1-3.1x | | -3x=-64+1 | | (5k^2-4k-1/5k^2-12k-7) | | 4y+12=-4(2y+5) | | 120x^2-116x-28= | | -x/5=75 | | B+3=2b-q | | 3xp=2qr-10qp | | 3log(2)x=3log(2)3 | | -7w+2=5w-10 | | 1.25(49+72)=c | | -3x=-12+1 | | x*e^(-x^2)/2)=0 | | 3px=2qr-10qx | | x*e^(-x^2)/2) | | 15+28h=29 | | 5x-(13-x)= | | -5(x+6)=2x-44 | | 3/12-7/24 | | -30x-4= | | 6x+6(-7+3x)=102 | | 9(3+X)=6x | | p^4p/p^-4 |

Equations solver categories